Analisis Pendapatan Usahatani Pisang di Kecamatan Sebatik Tengah Kabupaten Nunukan, Kalimantan Utara - Banyuriatiga Banyuriatiga (Fakultas Pertanian, Universitas Timor, 2023)
Bananas are one of the leading commodities from fruit plants in Nunukan Regency, where banana production in 2021 will reach 75,443 quintals. Bananas produced by farmers sold to Malaysia, which is directly adjacent to Nunukan Regency. Although bananas are a superior commodity that is widely cultivated by local residents, the selling price of bananas in Nunukan Regency relatively low. Prices for bananas range from IDR 3,000 to IDR 4,000/Kg. The purpose of this study was to analyze the income earned by banana farmers in Sebatik Tengah District, Nunukan Regency. The data used is primary data obtained from 50 respondent farmers using the accidental sampling method. The data analysis method used is the analysis of farm income by first calculating fixed costs and variable costs. The results showed that the income received by farmers for each planting was IDR 4,051,320 with total production 1,274 kg of bananas. The total cost to be incurred by farmers is Rp. 3,415,873.50, so that the income for the total costs earned by banana farmers in Sebatik Tengah District, Nunukan Regency is Rp. 635,446.6 for each planting period. When compared with the total costs that must be incurred, the average income earned by farmers is still relatively small. For this reason, it is necessary to do research on the income analysis of banana production to find out whether or not this farming is feasible.